Любовь и смерть в социальных сетях: [роман] / Наталья Андреева - Андреева Наталья Вячеславовна (Детектив-загадка, 2012)
Экземпляры: ф.6 (20240809) / Инвентарный номер: 4280 И / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44